Neighbourhood Europeanization through ENP: the case of Ukraine - Gawrich, Andrea; Melnykovska, Inna; Schweickert, Rainer (2009)
Abstract: We contribute to the literature of European Studies by introducing the approach of Neighbourhood Europeanization. Based on insights from Membership and Enlargement Europeanization, we reveal important inconsistencies of Neighbourhood Europeanization through the European Neighbourhood Policy (ENP) as well as a lack of robust empirical support for its effectiveness. We also define core dimensions and determinants of Neighbourhood Europeanization and implement this analytical framework for the case of Ukraine. Our analysis clearly demonstrates substantial asymmetries in the ENP for Ukraine across three dimensions we chose – democracy promotion, economic cooperation, and Justice and Home Affairs, which clearly reflect the inconsistency of the ENP concept, that is top-down formulation of EU interests combined with weak conditionality. However, our analysis shows that despite Ukraine’s growing frustration because of the lack of a membership perspective, there is a lot of room for keeping